Global compact on refugees: A transformative moment in refugee policy? - Heba Al Fara (University of Bath, Centre for Development Studies (CDS), 2022)
The adoption of the Global Compact on Refugees in 2018 aimed to address one of the biggest gaps in the international refugee regime, namely the misalignment of strongly integrated asylum policies with a weakly adopted standard policy of responsibility sharing among states. The Global Compact on Refugees is a voluntary framework that stems from the basic principles of humanity and international solidarity. It sets out a framework for more effectively sharing the burden of responsibility for safeguarding the rights of refugees among host communities serving as partners in implementing the Compact. The paper argues that the Compact represents a key transformation in the international approach to the global refugee regime through adoption of an integrated multi-stakeholder and partnership approach instead of a state focused one. The paper uses a top-down normative approach (focusing on global burden sharing and country level political constraints within existing political structures and institutions) to review the transformation from the old regime to the new one. It complements this with a bottom-up approach (focusing on policy implementation and the agency of civil society organizations) that draws on street level bureaucrat theory to illustrate the practical challenges that persist in effective implementation of the Compact's objectives.
Keywords: 330; Global Compact on Refugees; non-political framework; responsibility sharing; street level bureaucrat theory